KEPEMIMPINAN TRANSFORMASIONAL DAN KINERJA KOPERASI SEKOLAH: KAJIAN LITERATUR DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN - Rena Mey Sulistriana; Devi Listiani; Kufita Indi Zulfa; Damar Muthi'ah; Siswadi (STKIP Subang, 2026)
School cooperatives play a strategic role as a medium for economic learning that supports the development of entrepreneurial character, independence, and responsibility among students. However, in practice, the management of school cooperatives still faces various challenges, including low member participation, limited business innovation, and suboptimal organizational performance. This study aims to analyze the role of transformational leadership in improving the performance of school cooperatives through a literature review approach from the perspective of educational management. The method used is a literature study by reviewing relevant scientific sources such as journals, books, and previous research findings. The results indicate that transformational leadership contributes to improving cooperative performance by strengthening motivation, commitment, and member participation, as well as encouraging innovation and adaptive organizational culture. In addition, transformational leadership plays a role in building a shared vision and enhancing organizational effectiveness. Therefore, transformational leadership can be considered a relevant strategy to optimize the performance of school cooperatives.